Drones - A perspective on internal security - Ghosh, Debapriyo (The Indian Police Journal)
After cellphone technology boom the next big technological proliferation that is having immense potential to impact internal security in significant way is undisputedly the unmanned aircraft system (UAS), or, what is popularly recognized as drones. A result, of tremendous advancements in satellite based navigation. RF communication, very large scale intonation (VLSI) technologies in the recent past and a combination of multidisciplinary scientific paradigms like avionics, elections and telemetric. Drones have surely caught most honed internal security experts off grand. Presumably, Indian internal security apparatus is no exception and hence it is pertinent to explore vulnerabilities, or, to least acquire a clear understanding of the technology scenario up to the last man standing. Reproduced
Keywords: Unmanned aircraft system, UAS, Drones, Satellite based navigation, RF communication, Very large scale intonation, VLSI